PEMERIKSAAN MOBILE FORENSIK TERHADAP HANDPHONE SECARA PHYSICAL EXTRACTION DENGAN PERBEDAAN JENIS SOFTWARE - hasta saputra; Tris Zeno Alkindi; hery priyanto; agus dwisetiyono; panji zulfikar sidik (Pusat Laboratorium Forensik adan Reserse Kriminal Kepolisian Negara Republik Indonesia, 2021)
One of the electronic evidence found at the crime scene or related to cases, both criminal and civil, is cellphone evidence. To prove the presence or absence of the perpetrator's involvement with the use of mobile forensic examination techniques by physical extraction through analysis of digital traces in the form of call logs, SMS, phonebooks and other files where the data has been deleted. Several factors affect the physical extraction method, namely the software used. Mobile forensic examination software used to examine electronic evidence such as cellphones in forensic laboratories is Ufed Cellebrite 4 PC and XRY Microsystem. In this study, the level of success of the physical extraction method was investigated on evidence of a Nokia 105 (TA-1174) mobile phone with different software, namely Ufed Cellebrite 4 PC and XRY Micro Systemation. Extraction was carried out using the physical boot loader method on the memory in the Nokia 105 (TA-1174) mobile phone IMEI 1: 353810821569303 IMEI 2: 353810821569306. by using Ufed 4 Pc software and XRY Microsystemation, where the extraction results obtained, especially call logs, SMS and data that have been deleted using XRY Micrososystemation software, have the most complete success rate. This relates to the ability of each software in parsing/dumping and decoding processes.